LEGISLATIVE ACCOMMODATION OF INTERESTS OF ETHNIC MINORITIES IN THE COURSE OF FORMATION OF THE UKRAINIAN STATE AT THE BEGINNING OF 20 CENTURY - Lypchuk, O. I.; Lomaka, I. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2018)
In article it is noted that World War I, having extremely aggravated political and social and economic problems of belligerent parties, caused considerable rise of the national liberation movement. In the years of war, Galichina became an object of active international policy, at first as a component of the empire of Gabsburgov, and then as the sovereign state of the Ukrainian people. Also World War I accelerated political changes in Central and Eastern Europe and emergence of the Ukrainian state educations in Galichina. Introduction and developments of basic standard and legal documents in such spheres state and social and political life as formation of state governing bodies, justice, Armed Forces, social, economic, national and cultural and educational sites became the main result of legislative activity of power structures of West Ukrainian People’s Republic on nationalities. The mechanism of the state and national policy of West Ukrainian People’s Republic on non Ukrainian the population was based on democratic traditions of parliamentarism of the former Austria-Hungary. Such fundamental principles of national policy allowed power structures to direct the state construction to the democratic course, to make it socially oriented.